An Empirical Study on Investment Choices and Behavior of Salaried and Business Class Individuals - Sanjay Kumar; Sonal Gupta; Parul Mittal (International Journal of Management and Business Intelligence, 2023)
The income of households is increasing day by day because now, both male and female family member prefers to do work. This research analyzes the socio-economic profile of the investors and the impact of socio-economic profile on the investment pattern of salaried and business-class people. The study results show that there is no significant difference between the choice of respondents regarding different Investment alternatives and the occupation of the respondents except fixed deposit and chit funds. The results found that the investors of same occupation donot invest same percentage of their income but Investors lie in the same annual income category generally invest same percentage of their income. The income of the respondents depends on the occupation of the respondents. The capacity and the percentage of investment depends on the income level of respondents. The research found that the knowledge of individuals is increasing day by day as they start investing their money in diverse investment options.